Neutrophil-Lymphocyte Ratio as an Inflammatory Marker for Retrobulbar Optic Neuritis: Oral Presentation - Observational Study - Resident - I Gusti Agung Made SIddhi Putra; Indra Yti Mahayana (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Retrobulbar optic neuritis is a form of optic neuritis which part at the back of the eye become inflamed and demyelinated. The inflammatory response might be important for diagnosis and prognosis because in retrobulbar optic neuritis, everything seems normal anteriorly. This study aims to analyze the parameter changes of CBC in retrobulbar optic neuritis. Methods : Patients with retrobulbar optic neuritis who were admitted to the Yogyakarta Tertiary Hospital from January 2020 to March 2022 were included in this study. Age-matched healthy patients were recruited for comparison (controls). A venous blood sample was obtained as part of the examination at the first visit. The primary measure was white blood cells (WBC), while the secondary measures were neutrophil-to-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), haemoglobin, platelets, neutrophils, and lymphocytes counts. Results : 20 Patients were enrolled in case group, with mean age 27.75(±10.9)Y.O. and 13(65%) of them were female. overall, 4(20%) patients had bilateral involvement. Erythrocytes(p=0.45), Haemoglobin(p=0.17), Haematocrit(p=0.126), Thrombocyte(p=0.86), Monocyte(p=0.68), LMR(p=0.26), PLR(p=0.074) were insignificantly different between both group. Meanwhile Neutrophil(p=0.006) and NLR(p=0.021) were significantly higher in case group also Lymphocyte(p=0.05), Eosinophil(p=0.004)and Basophil(p=0.016) were significantly lower in case group. Conclusion : The inflammatory Parameters such as Neutrophil and NLR were found to be significantly higher in retrobulbar optic neuritis patients although other parameters like WBC were insignificantly different, even some parameters like Lymphocyte were significantly lower in retrobulbar optic neuritis. thus, these parameters especially NLR might be attributable to the pathogenesis of retrobulbar optic neuritis even when the WBC seems in normal limit.